2017
DOI: 10.1016/j.geomorph.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of suspended sediment transport in a glacierized Andean basin

Abstract: Suspended sediment transport can affect water quality and aquatic ecosystems, and its quantification is of the 13 highest importance for river and watershed management. Suspended sediment concentration (SSC) and dis-14 charge were measured at two locations in the Estero Morales, a Chilean Andean stream draining a small basin 15 (27 km 2 ) hosting glacierized areas of about 1.8 km 2 . Approximately half of the suspended sediment yield 16 (470 t year −1 km −2 ) was transported during the snowmelt period and half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…During the same period, the point clusters become significantly fuzzier, leading to negative slope values for BUS data in some cases (Figures 8 and 9). Such a pattern is associated with short-distance transport of sediment stock readily available for transport and becoming depleted during a flood (e.g., Mao and Carrillo, 2016). Finally, hysteresis at CRO is mainly anticlockwise whereas BUS and BDS data do not exhibit a clear prevalence of either type.…”
Section: Relation Between Suspended Sediment Concentration and Dischargementioning
confidence: 99%
See 3 more Smart Citations
“…During the same period, the point clusters become significantly fuzzier, leading to negative slope values for BUS data in some cases (Figures 8 and 9). Such a pattern is associated with short-distance transport of sediment stock readily available for transport and becoming depleted during a flood (e.g., Mao and Carrillo, 2016). Finally, hysteresis at CRO is mainly anticlockwise whereas BUS and BDS data do not exhibit a clear prevalence of either type.…”
Section: Relation Between Suspended Sediment Concentration and Dischargementioning
confidence: 99%
“…Conversely, Warburton (1990) found that the proglacial alluvial area of the Bas Glacier d'Arolla (Switzerland) was a significant source providing 23% of the suspended load. In addition, some studies that focus on associating sediment export fluctuations with water discharge drivers (snow-melt, ice-melt, precipitations) on the annual (Hodgkins et al, 2003), seasonal (Hodson et al, 1998) and sub-seasonal scales (Gao et al, 2013;Mao and Carrillo, 2016) provide insights into the time and space distribution of erosion processes. In addition, some studies that focus on associating sediment export fluctuations with water discharge drivers (snow-melt, ice-melt, precipitations) on the annual (Hodgkins et al, 2003), seasonal (Hodson et al, 1998) and sub-seasonal scales (Gao et al, 2013;Mao and Carrillo, 2016) provide insights into the time and space distribution of erosion processes.…”
Section: Sediment Budget and Comparison With Similar Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The rating curves of water discharge and SSC can reflect the physical environment in the river basin, which has a close relationship with the climate conditions, the yield of water, and sediment and human activities within the river basin (Girolamo, Pappagallo, & Porto, ; Landers & Terry, ; Mao & Carrillo, ). Figure shows the rating curves for the monthly water discharge versus SSC in the three tributaries during the 1950s–2000s.…”
Section: Resultsmentioning
confidence: 99%